2016
DOI: 10.2147/ott.s114303
|View full text |Cite
|
Sign up to set email alerts
|

Decreased miR-503 expression in gastric cancer is inversely correlated with serum carcinoembryonic antigen and acts as a potential prognostic and diagnostic biomarker

Abstract: BackgroundAltered expression of miR-503 has been linked to human carcinogenesis. In this present study, we aimed to detect the potential for miR-503 as a novel biomarker for gastric cancer (GC) patients.Materials and methodsThe relative mRNA level of miR-503 in serum and tissue of 68 GC patients and serum of 32 healthy volunteers was determined by real-time reverse transcription quantitative polymerase chain reaction.ResultsThe miR-503 level was significantly lower in the tissue and serum of GC than their coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 28 publications
(26 reference statements)
1
9
0
Order By: Relevance
“…In this study, the median value of CEA in the GC group was 2.74 (1.685-5.62) ng/ ml, which was higher than the 1.525 (1.09-2.385) ng/ml in the benign control, and the difference was statistically significant. When we used the clinically recommended 3.4 ng/ml as the cut-off value, the sensitivity was 0.409, the specificity was 0.942, and the AUC was 0.676, which are consistent with previous research [23,24]. Therefore, we believe that the level of CEA can help diagnose GC.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, the median value of CEA in the GC group was 2.74 (1.685-5.62) ng/ ml, which was higher than the 1.525 (1.09-2.385) ng/ml in the benign control, and the difference was statistically significant. When we used the clinically recommended 3.4 ng/ml as the cut-off value, the sensitivity was 0.409, the specificity was 0.942, and the AUC was 0.676, which are consistent with previous research [23,24]. Therefore, we believe that the level of CEA can help diagnose GC.…”
Section: Discussionsupporting
confidence: 88%
“…mir-503 is a member of the miR-16 family and has been reported to be associated with carcinogenesis; its aberrant expression has been observed in multiple tumors ( 31 , 32 ). While certain studies have observed that miR-503 is downregulated in several types of cancer, such as oral cancer, hepatocellular carcinoma, non-small cell lung cancer and endometrioid endometrial cancer ( 32 35 ), it has been observed that miR-503 expression is upregulated in adrenocortical carcinoma, parathyroid carcinoma and retinoblastoma ( 36 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of miR-503 inhibits the migration and invasion of hepatocellular carcinoma cells in vitro [35]. In addition, the down-regulation of miR-503 is associated with poor clinical outcome and inversely associated with the level of carcinoembryonic antigen in gastric cancer [36]. Whereas, miR-503 overexpression is identified in ALDH1-positive chemoresistant ovarian cancer cells [19], ALDH1(+) ovarian cancer cells comprise 0.4–4.0% of primary cancer cells [19].…”
Section: Discussionmentioning
confidence: 99%